2017
DOI: 10.1021/acs.jafc.7b02756
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Key Aroma-Active Compounds in Raw and Cooked Red Mullet (Mullus barbatus) by Aroma Extract Dilution Analysis

Abstract: Raw red mullet (Mullus barbatus) and its cooked samples, obtained from steam and oven cooking, were subjected to aroma and key odorant analysis for the first time using GC-MS-O. The extraction of the aroma compounds was carried out by the direct solvent extraction-solvent assisted flavor evaporation (DSE-SAFE) method. Principal component analysis (PCA) was used to determine the relations between cooking processes and fish aroma compounds. By applying the aroma extract dilution analysis (AEDA), 8 and 13 aroma-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 44 publications
2
42
0
1
Order By: Relevance
“…The high intensities of aldehydes in the four fish feed samples are in line with these having been reported as the main aroma compounds in aquaculture water, fish meat, fish oils, and meals (Selli et al, 2006 , 2009 ; Mahmoud and Buettner, 2016 , 2017 ; Salum et al, 2017 ), which might indicate that feeds are one of the primary enrichment sources of aldehydes in fish.…”
Section: Resultssupporting
confidence: 81%
“…The high intensities of aldehydes in the four fish feed samples are in line with these having been reported as the main aroma compounds in aquaculture water, fish meat, fish oils, and meals (Selli et al, 2006 , 2009 ; Mahmoud and Buettner, 2016 , 2017 ; Salum et al, 2017 ), which might indicate that feeds are one of the primary enrichment sources of aldehydes in fish.…”
Section: Resultssupporting
confidence: 81%
“…Zou et al () found that the oxidation of alcohol compounds caused formation of aldehydes or esters under high‐temperature conditions. Among the alcohol compounds, 1‐octen‐3‐ol was very important in the raw and cooked tuna samples due to the low threshold (1 μg/kg) (Salum et al, ). This compound is generally produced from arachidonic acid and is also the major volatile alcohol in several fish species (Guan, Ren, Li, & Mao, ; Salum et al, ; Zhuang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Heat used during fish processing exerts a great impact on the quality of products. Heat treatments cause the formation of volatile and nonvolatile compounds through enzymatic or nonenzymatic pathways, including Maillard reaction, Strecker degradation, and lipid oxidation in fish (Moreira, Valente, Castro‐Cunha, Cunha, & Guedes de Pinho, ; Salum, Guclu, & Selli, ). Several studies have been conducted on the quality characteristics of fish species as affect by heat treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the content of 1‑octen‐3‐ol, also known as C8‐complex low threshold volatiles, increased by 38.4 times compared with raw egg liquid. The production of 1‐octen‐3‐ol was usually attributed to degradation of linoleic acid or arachidonic acid (Edirisinghe, Graham, & Taylor, 2007; Wurzenberger & Grosch, 1982), and it is also often found in some heat‐treated foods, such as cooked red mullet, roasted duck (Liu et al., 2019; Salum, Guclu, & Selli, 2017). The above report at least proved that linoleic and arachidonic acid, which were abundant in egg lipids, might be regarded as precursors to 1‑octen‐3‐ol.…”
Section: Resultsmentioning
confidence: 99%